Analisis Penerimaan Siswa Baru dan Sarana Prasarana Bengkel Permesinan dengan Metode SWOT di SMK Nurul Islam - Alamul Yaqin; Akhmad Wasiur Rizqi; Hidayat Hidayat (Fakultas Teknik, 2023)
Nurul Islam Vocational School is a school that runs a business in the field of vocational education, namely Mechanical Engineering (TPM), Electrical Power Installation Engineering (TITL), Office Management Automation (OTKP). led to a decrease in the number of students in the SMK. The purpose of this study is to analyze existing internal and external resources and determine the appropriate method to be used to improve school quality so that it can attract public interest in using the SWOT method to survive and compete with other schools. In this research, different research methods, both quantitative and qualitative, are used to describe the realities of the area. The results obtained from the results of the SWOT analysis give an IFE value of 3.43, while an EFE value of 3.56. Therefore, the IE matrix of Nurul Islam Vocational School, several development strategies and solutions show that the SWOT matrix of Nurul Islam Vocational School is located in quadrant I. Vocational High School entrance fees are affordable is the second-choice alternative for parents if their child is not accepted at public high school as an effort to make it easier for student parents to choose a school.